USING OF EDUCATIONAL RESEARCH EVALUATION SYSTEM FOR VERIFICATION OF ELECTRONIC STUDY SUPPORTS - Milan, KLEMENT; CHRÁSKA, Miroslav (Trends in education, 2011)
The paper deals with the description of the verification of the electronic learning aids evaluation process, which could make the evaluation of these training materials unambiguous and quick. This system was developed on the basis of the theoretical analysis and synthesis of existing evaluation system for electronic learning aids.
Keywords: e-learning support; distance learning; e-learning; factor analysis; cluster analysis; Student t-test.